Hook (1991) - Steven Spielberg; Hoskins, Bob, 1942-; Caroline Goodall; Charlie Korsmo; Julia Roberts; Maggie Smith; Robin Williams; Dustin Hoffman (USA Amblin Entertainment, 2000)
Peter Pan (Williams) has grown up to be a cut-throat merger and acquisitions lawyer, and is married to Wendy's granddaughter. Captain Hook (Hoffman) kidnaps his children, and Peter returns to Never Land with Tinkerbell (Roberts). With the help of her and the Lost Boys, he must remember how to be Peter Pan again in order to save his children by battling with Captain Hook once again.
When Capt. Hook kidnaps his children, an adult Peter Pan must return to Neverland and reclaim his youthful spirit in order to challenge his old enemy.
J.M. Barrie
Language(s): English, French
Subtitle(s): English, Turkish, Arabic, Hindi
Keywords: Comedy; Family; Fantasy; Adventure